2018
DOI: 10.1111/ans.14893
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of preoperative CA19‐9 levels in evaluating resectability of gallbladder carcinoma

Abstract: Background: This study evaluated the predictive ability of preoperative carbohydrate antigen 19-9 (CA19-9) level in assessing tumour resectability in patients with gallbladder carcinoma (GBC). Methods: We retrospectively analysed preoperative serum levels of CA19-9 in 292 patients with potentially resectable GBC between January 2000 and March 2016 in our institution. All final diagnoses were confirmed by pathological examination. The optimal cut-off point of the CA19-9 for predicting resectability was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In our study the cutoff value of CA19–9 > 72 and CEA > 5 had high specificity but low sensitivity in detection of metastatic disease with a AUROC of 0.67 and 0.62 for CA19–9 and CEA respectively. Liu et al [ 13 ] found cut-off levels CA19–9 of 98.9 IU/ml, an independent predictor of resectability in GBC patients who underwent attempted resection with a sensitivity of 76.3% and specificity of 70.8%. They showed CA19–9 levels may predict R0 resection.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the cutoff value of CA19–9 > 72 and CEA > 5 had high specificity but low sensitivity in detection of metastatic disease with a AUROC of 0.67 and 0.62 for CA19–9 and CEA respectively. Liu et al [ 13 ] found cut-off levels CA19–9 of 98.9 IU/ml, an independent predictor of resectability in GBC patients who underwent attempted resection with a sensitivity of 76.3% and specificity of 70.8%. They showed CA19–9 levels may predict R0 resection.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CEA and CA19-9 concentrations may also predict the resectability of pancreatic cancers [ 31 33 ], whereas preoperative measurements of serum CEA, CA125, and CA19-9 concentrations can assist in evluating the resectability of cholangiocarcinomas, a type of biliary tract cancer [ 12 ]. Moreover, a study of 292 patients with stage I–IV GBC reported that preoperative CA19-9 could predict tumor resectability [ 13 ], although that study did not consider the effect of tumor-associated elevation of total bilirubin concentration on serum levels of CEA and CA19-9.. The radical resection rate of stage 0-I GBC is high, with these patients having a 5-year survival rate over 60% [ 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) are cancer-associated antigens, measurements of which have been widely used to determine the diagnosis and prognosis of patients with tumors of the digestive system, including pancreatic [ 7 ], bile duct [ 8 ], colorectal [ 9 ], and gastric [ 10 ] cancer. Moreover, measurements of CEA and CA19-9 concentrations can be used to evaluate the resectability of various cancers [ 11 , 12 ], including GBCs [ 13 ]. Radical resection is possible in most patients with early stage GBC (stage 0–I, AJCC 8 th ), with a satisfactory prognosis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Cox hazard proportional regression analysis showed that advanced tumor stages, high levels of CA199, and tumor location in gallbladder body or neck would indicate a poor prognosis. Studies have reported that CA199 is a prognosis related marker [21,28,29]. Moreover, Wang et al have reported that tumor location in gallbladder neck could be a prognosisrelated marker [21].…”
Section: Discussionmentioning
confidence: 99%